Man in search of Meaning value in the context of the culture of the postmodernity - О. А. Стасевська (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2016)
Analysis of recent publications indicates that at present scientists identify new round of spiritual crisis of society, a sign of which is that the person’s attention is not aimed at the realization of value meanings of their existence, and the material well-being, social status, personal achievements and their practical results. So, today is the most important question of understanding the person as a carrier of meaning and value creator in the context of the culture of postmodernity. The urgency of this task is conditioned by modern philosophy to understand the qualitative modification human postmodernity, identify its basic characteristics and its relation to the value foundations of life in the development of the Information Society, which transforms social orientations person.